Pilot hole study in friction welding processes: A review - Nur Syafiqah, Nor Sofian; Luqman Hakim, Ahmad Shah (Universiti Malaysia Pahang, 2024)
This paper reviews the progress of research on the use of pilot holes in metal joints during welding, focusing on Friction Stir Welding (FSW) and Friction Stir Spot Welding (FSSW) processes. The impact of pilot holes on the mechanical behaviour and macrostructure of metal joints under various welding conditions was thoroughly evaluated. The incorporation of pilot holes in FSSW processes, particularly for similar aluminum alloy joints, can increase mechanical performance by up to 50%. This technique also enhances tool longevity, improves joint quality, and optimizes surface finish. Several factors influenced by pilot hole optimisation are discussed, including the significance of the pilot-hole-to-keyhole (PTK) diameter ratio. Notably, pilot holes with a PTK ratio below 1 have demonstrated superior results. In dissimilar material FSSW, pilot hole conditions significantly influence material flow and intermixing, thereby affecting joint strength. This study also deliberates on the influence of pilot hole diameter on the welding process. Finally, several recommendations are offered in light of these findings to guide future research and application in this field.